Heterogeneity of stem cells in severe combined immunodeficiency. - Incefy, G S (1976)
Two patients with severe combined immunodeficiency disease (SCID) having variable B-cell development have been shown to have marrow precursors of lymphoid cells which can be induced in vitro by thymic factors to express certain T-cell surface characteristics (HTLA+ phenotypes). Their marrow cells could not, however, be induced by these same factors to develop the E-rosette marker or functional activities of T lymphocytes. The marrow of these children also showed, when compared to that of normal adults, a different distribution of cellular elements on density gradient fractionation. The findings support the view that the disorder under study has a different pathogenesis from other forms of SCID previously analysed.